2003
DOI: 10.1103/physrevd.68.034009
|View full text |Cite
|
Sign up to set email alerts
|

Signals of new physics in global event properties inppcollisions in the TeV energy domain

Abstract: In the framework of the weighted superposition mechanism of different classes of minimum bias events (or substructures), described by the negative binomial multiplicity distribution, in possible scenarios for pp collisions in the TeV energy domain, we explore global properties of an eventual new class of events, characterised by high hadron and clan densities, to be added to the soft (without minijets) and semihard (with minijets) ones. It turns out that the main signal of the mentioned new physical expectatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…k −1 = a + b ln n in [20], and the Pythia Monte Carlo [22], respectively dotted line and cross in Fig. 3c) give a monotonically decreasing k; for a discussion of the situation in which k continues to decrease at high energy and reaches values smaller than 1, see [21].…”
Section: The Physicsmentioning
confidence: 99%
“…k −1 = a + b ln n in [20], and the Pythia Monte Carlo [22], respectively dotted line and cross in Fig. 3c) give a monotonically decreasing k; for a discussion of the situation in which k continues to decrease at high energy and reaches values smaller than 1, see [21].…”
Section: The Physicsmentioning
confidence: 99%
“…This violation of the virtuality conservation law spoils of course the validity of the energy-momentum conservation law, which, in the SPS model, uniquely determines the rapidity of a produced parton, given its virtuality and the virtuality and rapidity of its germane parton -see Eq. (108). In the GSPS model the two produced partons at each splitting are independent both in virtuality and in rapidity; however, the rapidity of each parton is bounded by the extension of phase-space fixed by its virtuality and the virtuality of the parent parton:…”
Section: The Gsps Model: Generalised Clansmentioning
confidence: 99%
“…In [1] we concluded that an early occurrence of the limitN sh → 1 in FPS is of particular interest and leads in our framework to the onset of a new class of events with quite remarkable properties controlled by k th < 1, the effective benchmark of the new class of events.…”
Section: Antecedents: Global Properties In Full Phase-spacementioning
confidence: 99%
“…4 are shown the three components and their superposition predicted by Pythia at 14 TeV in the interval |η| < 0.9. We have taken the results from [1], where Pythia version 6.210 [8] was run with default parameters using model 4 with a double Gaussian matter distribution. This set-up gives a reasonable description of lower energy MD data.…”
Section: Pythiamentioning
confidence: 99%
See 1 more Smart Citation